Difluoroboron β-diketonate polylactic acid oxygen nanosensors for intracellular neuronal imaging - Meng Zhuang (Nature Portfolio, 2021)
Abstract Critical for metabolism, oxygen plays an essential role in maintaining the structure and function of neurons. Oxygen sensing is important in common neurological disorders such as strokes, seizures, or neonatal hypoxic–ischemic injuries, which result from an imbalance between metabolic demand and oxygen supply. Phosphorescence quenching by oxygen provides a non-invasive optical method to measure oxygen levels within cells and tissues. Difluoroboron β-diketonates are a family of luminophores with high quantum yields and tunable fluorescence and phosphorescence when embedded in certain rigid matrices such as poly (lactic acid) (PLA). Boron nanoparticles (BNPs) can be fabricated from dye-PLA materials for oxygen mapping in a variety of biological milieu. These dual-emissive nanoparticles have oxygen-insensitive fluorescence, oxygen-sensitive phosphorescence, and rigid matrix all in one, enabling real-time ratiometric oxygen sensing at micron-level spatial and millisecond-level temporal resolution. In this study, BNPs are applied in mouse brain slices to investigate oxygen distributions and neuronal activity. The optical properties and physical stability of BNPs in a biologically relevant buffer were stable. Primary neuronal cultures were labeled by BNPs and the mitochondria membrane probe MitoTracker Red FM. BNPs were taken up by neuronal cell bodies, at dendrites, and at synapses, and the localization of BNPs was consistent with that of MitoTracker Red FM. The brain slices were stained with the BNPs, and the BNPs did not significantly affect the electrophysiological properties of neurons. Oxygen maps were generated in living brain slices where oxygen is found to be mostly consumed by mitochondria near synapses. Finally, the BNPs exhibited excellent response when the conditions varied from normoxic to hypoxic and when the neuronal activity was increased by increasing K+ concentration. This work demonstrates the capability of BNPs as a non-invasive tool in oxygen sensing and could provide fundamental insight into neuronal mechanisms and excitability research.